Pengaruh Kepemimpinan, Komunikasi Interpersonal dan Lingkungan Kerja Terhadap Motivasi Kerja Pegawai Direktorat Jenderal Perkeretaapian Kementerian Perhubungan - Moronney, Patrick; Wahyudin, Dian (Reformasi Administrasi, 2025)
The aim of this research is to find out how much influence Leadership, Interpersonal Communication and the Work Environment have on the Work Motivation of Employees of the Directorate General of Railways, Ministry of Transportation. In this research method, the research approach chosen is associative quantitative, namely research that looks for the relationship between one variable and another variable. This research was conducted at the Office of the Directorate General of Railways, Ministry of Transportation. The research and observations were carried out from May 2024 to August 2024. The sampling technique used in this research was the census method with 166 respondents, and the data analysis technique used was multiple linear regression analysis technique using SPSS version 25 software. Based on From the analysis carried out, it can be concluded that leadership, interpersonal communication and the work environment affect the work motivation of employees of the Directorate General of Railways, Ministry of Transportation, both partially and simultaneously.